2015
DOI: 10.1186/s12889-015-1885-0
|View full text |Cite
|
Sign up to set email alerts
|

Cost for physician-diagnosed influenza and influenza-like illnesses on primary care level in Germany – results of a database analysis from May 2010 to April 2012

Abstract: BackgroundSeasonal influenza is one of the most significant infectious diseases in Germany; epidemic outbreaks occur every winter and cause substantial morbidity and mortality. However, published data from Germany on the current economic burden of influenza and the costs per episode are lacking.MethodsA retrospective database analysis was conducted using a longitudinal electronic medical records database (IMS Disease Analyzer). Patients with influenza, diagnosed by German office-based physicians using ICD-10 J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(66 citation statements)
references
References 27 publications
(32 reference statements)
3
48
0
15
Order By: Relevance
“…To our knowledge, the present study is the first population-based study to demonstrate that the protective effect of influenza vaccine in reducing all-cause mortality, influenza-related hospitalization, LOS, and medical expenditure in elderly individuals with disability. Medical expenditure of individuals with influenza, including those with influenza-related complications such as pneumonia [24], respiratory diseases [25], respiratory failure [26,27], heart disease [28][29][30], hemorrhagic stroke [31], and ischemic stroke [30], has often led to higher spending. In our study, we found that influenza vaccination was associated with reductions in all-cause mortality, influenza-related hospitalization, LOS, and medical costs decreased among elderly individuals with a disability (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the present study is the first population-based study to demonstrate that the protective effect of influenza vaccine in reducing all-cause mortality, influenza-related hospitalization, LOS, and medical expenditure in elderly individuals with disability. Medical expenditure of individuals with influenza, including those with influenza-related complications such as pneumonia [24], respiratory diseases [25], respiratory failure [26,27], heart disease [28][29][30], hemorrhagic stroke [31], and ischemic stroke [30], has often led to higher spending. In our study, we found that influenza vaccination was associated with reductions in all-cause mortality, influenza-related hospitalization, LOS, and medical costs decreased among elderly individuals with a disability (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…However, probably because of the long-lasting symptoms, 63% of patients received antibiotics, 47% antitussives, and 17% steroids. A retrospective database analysis of drug prescriptions in influenza and influenza-like illnesses of much shorter duration of coughing in Germany [17] showed that in that cohort, around 50% of patients did not receive prescriptions. However, among those who did receive drugs, 40% received antibiotics (63% in our study) and 12% received antitussives (37% in our study).…”
Section: Discussionmentioning
confidence: 99%
“…Die betroffenen Altersgruppen, die Gesamtzahl der Erkrankungen und auch deren Schwere können in verschiedenen Jahren stark variieren. Je nach zirkulierendem Virustyp und Zeitdauer der erhöhten Viruszirkulation kommt es zu mehr als 20.000 bis 30.000 geschätzten Influenza-bedingten Hospitalisierungen, einer auf Bevölke-rungsebene messbaren Übersterblichkeit und erheblichen direkten und indirekten Kosten für das Gesundheitswesen und die Volkswirtschaft [2,3]. Eine zeitnahe Surveillance ist daher wichtig zur Beurteilung der Situation und für die Anpassung von Präventionsmaßnah-men.…”
Section: Hintergrundunclassified